1992
DOI: 10.1037/0012-1649.28.3.430
|View full text |Cite
|
Sign up to set email alerts
|

The role of otitis media in the development of expressive language disorder.

Abstract: The role of otitis media (OM) was investigated in a group of preschool children with a rigorously defined language impairment: developmental expressive language disorder (ELD). No differences in the frequency, duration, or timingof medically documented episodes of OM were found between 65 ELD and 50 normal children. However, longitudinal analyses with the ELD children revealed a relation between OM and expressive language improvement. The strongest positive predictor of language improvement between 2 and 3 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 46 publications
1
10
2
Order By: Relevance
“…However, the evidence does not support such a relation for specific language delay. In our sample of 91 normal children and 93 two-year-olds with specific expressive delay there were no differences that approached significance on birth weight, rates of prematurity, or obstetric complications (Wliitehurst et al 1992). Likewise, found that neither pre-nor perinatal problems distinguished two-year-olds with specific language delay from normally developing controls.…”
Section: Prenatal and Perinatal Historycontrasting
confidence: 62%
“…However, the evidence does not support such a relation for specific language delay. In our sample of 91 normal children and 93 two-year-olds with specific expressive delay there were no differences that approached significance on birth weight, rates of prematurity, or obstetric complications (Wliitehurst et al 1992). Likewise, found that neither pre-nor perinatal problems distinguished two-year-olds with specific language delay from normally developing controls.…”
Section: Prenatal and Perinatal Historycontrasting
confidence: 62%
“…), socio‐economic status (SES) (Paul and Fountain ), gestural communication (Thal and Tobias ), and the presence of otitis media (Lonigan et al . ). Multiple factors may be involved.…”
Section: Introductionmentioning
confidence: 97%
“…In a follow-up of the same sample, the researchers considered whether otitis media might act as a nongenetic risk factor for early language delay. They found that children with early expressive language delay did not differ from controls in the frequency, duration, or timing of episodes of otitis media, but history of middle ear disease between 12 and 18 months of age predicted expressive language improvement in the language delayed group (Lonigan, Fischel, Whitehurst, Arnold, & Valdez-Menchaca, 1992). They concluded that the population of children with language delay may contain a mixture of two etiological groups.…”
mentioning
confidence: 99%